Keluarga Berencana Program as a Social Strategy for Sustaining the Tradition of Early Marriage among the Bangkalan Community - Ach Mudhoffar; Syamsu Madyan; Zukhriyan Zakaria (KURAS Institute, 2025)
Early marriage in Indonesia remains a serious problem with multidimensional impacts, ranging from reproductive health to educational sustainability and structural poverty. The purpose of this study is to analyze the legitimacy of Family Planning or Keluarga Berencana (KB) program practice from an Islamic perspective as a response to early marriage, describe family planning practices as a social strategy for maintaining tradition, and explore the adaptive rationale behind the use of family planning to mitigate the biological and social impacts of early marriage. The research method used is empirical legal research with a qualitative approach. Data were obtained through in-depth interviews, field observations, and documentation studies, then analyzed using the maqāṣid al-sharī‘ah framework and social agency theory. The results show that the people of Gunung Sereng Village understand family planning not only as a means of birth control but also as a social mechanism to bridge tradition with state regulations. Theologically, family planning practices are seen as aligned with the maqāṣid al-sharī‘ah in preserving the soul (ḥifẓ al-nafs) and offspring (ḥifẓ al-nasl). From a social agency perspective, communities demonstrate an active capacity to negotiate religious norms, traditions, and state law through the use of family planning as a form of adaptation and soft resistance to state policies. Thus, this research enriches the study of Islamic family law and legal pluralism in Indonesia and provides a practical contribution to the formulation of marriage policies and family planning programs that are more contextual and sensitive to the socio-cultural realities of rural communities.